EVALUASI PELAKSANAAN KEGIATAN PERTUKARAN PELAJAR PROGRAM MERDEKA BELAJAR-KAMPUS MERDEKA (MBKM) PADA MAHASISWA KESEHATAN INBOUND DI UNIVERSITAS MUSLIM INDONESIA - Nurmiati Muchlis; Nurjannah Abna; Rezky Aulia Yusuf; Awaluddin Syamsu; Lukman Chalid (PT.Mantaya Idea Batara, 2022)
Innovation to improve the education sector in Indonesia is continues. One of them is the implementation of the Independent Learning-Independent Campus (MBKM) in 2020 in all universities, both public and private. The Indonesian Muslim University (UMI) as one of the largest private universities in eastern Indonesia also participates in implementing this program, one of which is the student exchange program. In this student exchange program, there are as many as 30 students who take part in conducting online lectures at UMI. To improve the quality of program implementation at UMI, of course, evaluation is very necessary. Therefore, this study reports describing the quality of the program from the experiences of students(i) who participated in the student exchange program, Merdeka Learn Campus Merdeka (MBKM) at UMI. The population in this study were inbound students (i) who took part in the student exchange program at the Indonesian Muslim University who came from the health faculties, totaling 7 people. Questionnaires from the Ministry of Research and Technology (SPADA) were used in this study, with a total of 21 questions. Conclusion; 1). Health students feel that this student exchange program benefits their competencies and skills; 2). This student exchange program is important for their preparation after graduating from S1; 3). Students are worried about spending more. Suggestion; 1). Wider socialization is needed for students regarding this program; 2). Dissemination that reaches a wide reach is carried out on the online channel of the Ministry of Education and Culture as well as online/offline socialization by universities.